Outcomes of 43 small breed dogs treated for splenic hemangiosarcoma. Issue 6 (20th June 2020) - Story, Ashton L.; Wavreille, Vincent; Abrams, Brittany; Egan, Angela; Cray, Megan; Selmic, Laura E.
Abstract: Objective: To determine outcome and prognostic factors in small breed dogs in which hemangiosarcoma was diagnosed and whether outcomes differed between small and large breed dogs with splenic hemangiosarcoma. Study design: Bi‐institutional retrospective study. Animals: Forty‐three small breed (<20 kg) and 94 large breed client‐owned dogs. Methods: Medical records were reviewed to identify dogs treated with splenectomy for splenic hemangiosarcoma. Data acquired included signalment, preoperative staging, bloodwork results, surgical findings, histopathologic findings, administration of chemotherapy, presence/absence of metastatic disease, and survival time (ST). Cox proportional hazards regression analysis was performed to assess prognostic factors associated with survival. Results: The overall median ST was 116 days and 97 days for small and large breed dogs, respectively. The ST for dogs treated with surgery and chemotherapy was 207 and 139 days for small and large breed dogs, respectively. The disease‐free interval (DFI) was 446 and 80 days for small and large breed dogs, respectively. Dog size was associated with DFI ( P = .02) but not with ST ( P = .09). The presence of metastasis at diagnosis was associated with decreased ST in small ( P = .03) and large ( P = .0009) breed dogs. Administration of chemotherapy ( P = .02) was associated with increased ST ( P = .02) in small breed dogs. Conclusion: The ST was not different in small and large breed dogs with splenic hemangiosarcoma treated with splenectomy and chemotherapy. Clinical significance: Prognosis remains poor despite aggressive therapies in small and large breed dogs.